Enseñanza de la filosofía en Norte de Santander, Colombia: caso provincia de Pamplona (2022)
The purpose of this article is to present the characterization of philosophy education in the department of Norte de Santander, Colombia, through the answer to the question “how do teachers in the Pamplona area teach philosophy in Norte de Santander?” using a mixed research method. These partial research results in the Pamplona area only focus on the generalities of the philosophical work within the research apparatus developed in 33 schools in the North Santander region. With them, it is intended to cover the design of the current philosophy teacher profile in the region, which follows the order of age, gender, undergraduate degree obtained, which postgraduate studies have been completed, the teaching status to which they belong, if they are appointed or provisional teacher, if they have made the exercise of publishing texts, and the motivation for writing and publishing. The main conclusion of this research is that the teaching of philosophy in schools of Norte de Santander should be strengthened through different strategies that start from the academy, such as the formation of a professional profile in philosophy, the creation of postgraduate studies in this subject, in addition to nurturing the importance of the research culture as a process of improvement of philosophical teaching.